Adaptation of Work Values Instrument in Indonesian Final Year University Students - Sulistiobudi, Rezki Ashriyana; Hutabarat, Harlin Nikodemus (Frontiers in Psychology, 2022)
Background. One of the preferences working in the Z generation is based on their motivational work values. The relevance of job choices with the work values will contribute to student career planning. The work value instrument among generations is one of the popular instruments used to measure final year students' work value, yet few studies of the psychometric properties of non-English language versions of this instrument. This study's objectives were to adapt a questionnaire of work value in Indonesian final year university students. Methods. The number of participants in this study was 316 students in Indonesia, comprised of final year students from various majors who were selected by quota sampling. The instrument consisted of 5 dimensions of value, including Leisure, Extrinsic Rewards, Intrinsic Rewards, Altruistic Rewards, and Social Rewards. The reliability analysis was performed using Mc.Donald’s omega, the evidence of validity was obtained from test content, internal structure through confirmatory factor analysis (CFA), and evidence-based on relation to other variable has conducted the correlation between Work Value and Career Development Learning using Pearson Correlation coefficient. Result. The results showed that the work values instrument had good psychometric properties, including good reliability, good content validity and internal structure. In CFA, the two-factor structure showed satisfactory model fit. Moreover, the correlation of Work Value with Career Development Learning build stronger validity evidence on this instrument. Conclusion. The adapted instrument can be used practically to identify work value preferences of final year students to help them choose a work preference and set up the career planning before graduating. The result could be of interest for the researcher in work value, motivational work and career areas in higher education. To the best of our knowledge, there have been no reports about the adaptation of work value instruments in Indonesian final-year university students.